Principles in Planning Library Education Programs in the Muslim World - Ali I. Namlah (International Institute of Islamic Thought, 1984)
ABSTRACT Four major principles for planning library education programs in [the] Muslim World are considered of importance: the environmental needs, the application of programs, the cultures, backgrounds and traditions of the nation, and the future changes. The Muslim World is acquiring expertise largely from non-Muslim nations through recruiting expert planners or through sending their students to developed countries to acquire knowledge, then apply it. Both approaches are seen to have some problems at the time of acquisition and application of planned programs. These problems are discussed and planners are expected to be aware of these principles before they start their plans. Blind application of library technology is considered the main reason for the failure of library education programs in some Muslim World countries. A balance of application, in accordance with the four principles, is recommended. Introduction I. The Muslim World What is meant by the phrase “the Muslim world” is those countries which have a high percentage of Muslims compared to non-Muslims. The Muslim World is a part of what is called “less developed countries,” “developing countries,” the “Third World,” or the “South.” The phases are used to refer to those countries-including the Muslim world-which are less advanced in technologies due to the existence of many factors, some of which are: ...